The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.7202
|View full text |Cite
|
Sign up to set email alerts
|

Brachyury identifies a class of enteroendocrine cells in normal human intestinal crypts and colorectal cancer

Abstract: Normal homeostasis of adult intestinal epithelium and repair following tissue damage is maintained by a balance of stem and differentiated cells, many of which are still only poorly characterised. Enteroendocrine cells of the gut are a small population of differentiated, secretory cells that are critical for integrating nutrient sensing with metabolic responses, dispersed amongst other epithelial cells. Recent evidence suggests that sub-sets of secretory enteroendocrine cells can act as reserve stem cells. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The Sox9-EGFP mouse model offers the opportunity to study and isolate progenitor cells (Sox9-EGFP Sublow ) and Sox9-EGFP High cells that contain EEC cells and an activatable reserve stem cell population [ 25 ]. A recent study suggested that subsets of secretory EEC cells can act as reserve stem cells in humans [ 45 ]. Interestingly, we observed an increased proportion of Sox9-EGFP High cells in S phase of the cell cycle in old mice, yet no expansion in cell number.…”
Section: Discussionmentioning
confidence: 99%
“…The Sox9-EGFP mouse model offers the opportunity to study and isolate progenitor cells (Sox9-EGFP Sublow ) and Sox9-EGFP High cells that contain EEC cells and an activatable reserve stem cell population [ 25 ]. A recent study suggested that subsets of secretory EEC cells can act as reserve stem cells in humans [ 45 ]. Interestingly, we observed an increased proportion of Sox9-EGFP High cells in S phase of the cell cycle in old mice, yet no expansion in cell number.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in these tumors, Brachyury has been reported as an independent biomarker of poor prognosis (Kilic et al ., ; Haro et al ., ; Palena et al ., ; Pinto et al ., , ,b). Brachyury acts as a key player in the epithelial–mesenchymal transition (EMT) and metastasis formation (Fernando et al ., ; Imajyo et al ., ; Shimoda et al ., ; Du et al ., ; Palena et al ., ; Pinto et al ., ; Shao et al ., ; Xu et al ., ), also playing an important role in promoting stem cell properties (Sarkar et al ., ; Shimoda et al ., ; Jezkova et al ., ; Pinto et al ., ,b) and resistance to cytotoxic‐based therapy (Fernando et al ., ; Roselli et al ., ; Pinto et al ., ,b). Based on Brachyury oncogenic behavior, an anti‐Brachyury vaccine (GI‐6301) was developed and is currently in Phase II clinical trial (http://www.clinicaltrials.gov, 2015 – NCT02383498) for patients with chordoma (Heery et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Post-developmentally, brachyury is expressed in the testes and some thyroid tissues, but is undetectable in all other non-neoplastic adult tissues (Edwards et al, 1996; Hamilton et al, 2015). Interestingly, recent studies have reported the expression of brachyury in several epithelial cancers where it promotes growth, confers resistance to chemo- and radiotherapy, and drives epithelial-to-mesenchymal transition (EMT) (Cho et al, 2010; Fernando et al, 2010; Haro et al, 2013; Huang et al, 2013; Imajyo et al, 2012; Jezkova et al, 2016; Kobayashi et al, 2014; Larocca et al, 2013; Li et al, 2016; Miettinen et al, 2015; Palena et al, 2014; Park et al, 2008; Pinto et al, 2015; Pinto et al, 2014; Pires and Aaronson, 2014; Roselli et al, 2012; Sarkar et al, 2012; Shao et al, 2015; Shimoda et al, 2012; Vujovic et al, 2006; Xu et al, 2015; Yoshihama et al, 2016); however, the mechanistic details of how brachyury mediates these features of tumor progression have not been fully elucidated. Furthermore, the lack of brachyury expression in most adult non-neoplastic tissues and exclusive tumor-specific expression underscores its value as a potential diagnostic and therapeutic target in cancer.…”
Section: Introductionmentioning
confidence: 99%